Sexually transmitted infections are not associated with US holidays - Michael Mohseni; Jessica Monas; Nicole Hodgson; Brittany Beel; Alyssa McGary; Johnathan M. Sheele (Scientific Reports)
Abstract Few investigations exist on the temporal association of sexually transmitted infections (STIs) with holidays, special events, or seasons. Limited studies suggest a summer and fall predominance to STIs, but associations with calendar holidays are unclear. We sought to examine the rates of gonorrhea, chlamydia, and trichomonas after US holidays, patient birthdays, and other major calendar events. We retrospectively examined patients aged 12–120 years of age (with an encounter at our institution between July 13, 2006 and September 23, 2023) that had a polymerase chain reaction or nucleic acid amplification test for Neisseria gonorrhea, Chlamydia trachomatis, or Trichomonas vaginalis or who had a rapid antigen or positive urine microscopy for Trichomonas vaginalis performed. We examined the STI testing date for a temporal relationship between US holidays and patient birthdays. We used each STI’s incubation period plus 14 days to determine if it was associated with the primary outcomes. Among 153,344 encounters, the majority were women (n = 130,182; 85%), single (n = 102,813; 67%), and White (n = 133,103; 90%). Mean (SD) age was 29 (10) years. For gonorrhea, Mardi Gras was associated with a lower risk (OR = 0.72; p = 0.015), while Memorial Day was associated with a higher risk of a positive test (OR = 1.38; p = 0.002). For chlamydia, the patient’s birthday (OR = 1.11; p = 0.02) was associated with an increased risk of a positive test. Finally, National Girlfriend’s Day (OR = 0.77; p = 0.005) was associated with a decreased risk of a positive test for trichomonas. On logistic regression, a weekend visit was found to be significantly associated with a positive test for gonorrhea, chlamydia, and trichomonas (p < 0.001 for all). No consistent association was found between calendar holidays or patient birthdays and the risk of positive testing for STIs.